Beneficiation of Gold Bearing Ores Associated with the Tertiary Volcanism in South Sardinia (Italy) (ABSTRACT PAGE) - S. di Giovanni; G. Zonnedda; M. Ghiani; A. Serci; R. Peretti (International Mineral Processing Congress, 2003)
"An interesting occurrence of gold bearing ores of economic interest has recently been discovered in the Serrenti- Furtei district, central-southern Sardinia (Italy). The upper part of the orebodies are leaner and fairly porous, and are undergoing intense oxidation processes. In the lower parts sulphide ores predominate, chiefly enargite-luzonite and pyrite and these have a more compact structure. The passage from the oxidized to the sulphide zones, is rather irregular and difficult to delineate. The gold, generally occurring in its native form, is found in small grains. Mineral reserves in the area concerned were originally estimated to total 2.77 Mt: 0.63 Mt of oxide minerals with average gold content of 2.75 g/t and 2.14 Mt of sulphide ores with average gold grade of 3.18 g/t.Recovery of the valuable metals is a complex problem.The effectiveness of a variety of gold extraction techniques has been evaluated conducting tests on batches of ore representative of the different orebody depths obtained from core samples.The techniques investigated were: heap and vat leaching; flotation and flotation followed by leaching of the flotation tailings. The findings indicate that:• the gold contained in the ores in the upper oxidized zones of the deposit can be efficiently recovered by direct cyanidation via heap or vat leaching;• the sulphide ores in the deeper portions, that are not amenable to direct cyanidation but contain enargite concentrations of potential economic interest can be processed by means of flotation to produce a gold/copper bulk concentrate;• beneficiation of the difficult-to-treat minerals contained in the transition zone requires some knowledge of their intrinsic properties. A distinction should be made between the ores containing minor amounts of enargite which appear to be amenable to vat leaching and those with relatively higher enargite content which are processed using bulk flotation of the gold and copper minerals followed by vat leaching of the resultant tailings."